2004
DOI: 10.1299/jsmec.47.792
|View full text |Cite
|
Sign up to set email alerts
|

Design of Digital High-Gain PD Control Systems Using Analytical Approach

Abstract: It is known that a continuous stable high-gain PD control system may become unstable when the controller is implemented digitally. Recent works consider this problem and determine the stability regions of such systems. In most cases the stability regions are obtained numerically. This work introduces a new analytical approach for obtaining the stability criteria for digital systems. The approach is based on the critical constraints of simplified version of Jury test and makes use of the capabilities of MATLAB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 12 publications
(23 reference statements)
2
16
0
Order By: Relevance
“…For D > 0, one can obtain the real root of the cubic equation (10) by substitution for z by the one that has real value from the three solutions (z 1 ,z 2 ,z 3 ) in Eq. (14). It is to be noted that this real root can represent root 1 or root 3 .…”
Section: Appendix Imentioning
confidence: 99%
See 2 more Smart Citations
“…For D > 0, one can obtain the real root of the cubic equation (10) by substitution for z by the one that has real value from the three solutions (z 1 ,z 2 ,z 3 ) in Eq. (14). It is to be noted that this real root can represent root 1 or root 3 .…”
Section: Appendix Imentioning
confidence: 99%
“…In practice, it has been demonstrated that a system may become unstable when the feedback gains are high (12) . It is shown that a stable highgain continuous PD control system (first and second-order systems) may become unstable when implemented digitally (12) - (14) . In Refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, it has been demonstrated that a system may become unstable when the feedback gains are high (11) . It is shown that a stable highgain continuous PD control system (first and second-order systems) may become unstable when implemented digitally (11) - (13) . In Refs.…”
Section: Introductionmentioning
confidence: 99%
“…(13) to cases involving flexible systems. We shall show that a collocated PD control of single-rigid/single-flexible mode system which guarantees stability may become unstable when implemented digitally even in cases involving small gains.…”
Section: Introductionmentioning
confidence: 99%